Development Of LKPD Based On Contextual Teaching And Learning To Improve The Learning Result Of Class V SDN Karawaci 1 - Imam Nur Rahman; Sofwatillah Amin; Henny Setiani (Institute of Computer Science (IOCS), 2022)
Student Activity Sheets are teaching materials as a guide for students used to conduct investigations or problem-solving. The science worksheets used in class V are currently only focused on material texts and questions and do not develop student activities related to the student environment, so it is necessary to develop contextual learning-based worksheets on hot material science learning and its changes through Research and Development (R&D). to determine the feasibility of the content, the feasibility of presenting the assessment of contextual learning and the feasibility of graphics. Student and teacher responses after using LKPD classically 90.9% (very interesting) content feasibility, presentation feasibility, contextual learning assessment, and graphic feasibility from each validator, namely validator 1 of 86.96% (very feasible), validator 2 of 84 .78 (very decent), and the teacher's assessment of 89.15% (very decent). Based on the analysis of experts, media, and materials, LKPD meets the criteria to be used as teaching materials in science subjects